SOCIAL CAPITAL IN THE DEVELOPMENT OF KEMBANG SIALANG JOINT BUSINESS GROUP PEKANBARU CITY - Ningtias H, Septia Ayu; Susanti, Rina (Universitas Tanjungpura, 2023)
This article describes the potential of social capital in trust, networks, and norms for developing KUB Kembang Sialang business. Social capital is examined in the pattern of membership and group relationships with partners using a qualitative approach to collecting data through in-depth interviews and observations